2006
DOI: 10.1002/ajim.20308
|View full text |Cite
|
Sign up to set email alerts
|

How many work‐related injuries requiring hospitalization in British Columbia are claimed for workers' compensation?

Abstract: When compared with hospital discharge records, the compensation agency underreported incidents of serious work-related injuries by 10-15% among the sawmill workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(35 reference statements)
3
15
1
Order By: Relevance
“…This result was slightly lower than the 60% of respondents who filed a claim after an eligible work-injury reported by Shannon and Lowe [2002], and significantly lower than the 85% of respondents with hospitalizations in British Columbia sawmill workers reported by Alamgir et al [2006]. However, given the limited information we have on the types of injuries related to work absences in our dataset, or the consequences of work injury (e.g., hospitalizations) it is difficult to directly compare our results with these other reports.…”
Section: Discussioncontrasting
confidence: 76%
“…This result was slightly lower than the 60% of respondents who filed a claim after an eligible work-injury reported by Shannon and Lowe [2002], and significantly lower than the 85% of respondents with hospitalizations in British Columbia sawmill workers reported by Alamgir et al [2006]. However, given the limited information we have on the types of injuries related to work absences in our dataset, or the consequences of work injury (e.g., hospitalizations) it is difficult to directly compare our results with these other reports.…”
Section: Discussioncontrasting
confidence: 76%
“…As there are likely more work-related injuries reaching hospitals than the compensation agency reports [9,10], and hospital records are collected independently, this investigation provided a more comprehensive description of serious work-related injuries. Validity and reliability of administrative and electronically collected databases have been established in some previous studies [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The methods are described in more detail by Alamgir et al [10,13]. Individual admissions were identified as work-related using ICD-9 external cause of injury codes that indicate place of occurrence [12]; and the responsibility of payment schedule, which identifies workers' compensation as being responsible for payment.…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports from Canada have demonstrated that workers compensation claims do not represent all injuries and illnesses that may be eligible for compensation, with workers with injuries perceived as less severe, employed in precarious employment relationships or with injuries involving a more complex etiology being less likely to file compensation claims 22−25) . Specifically focusing on age differences, a study conducted in BC found that older workers were less likely than their younger counterparts to claim compensation for injuries that resulted in hospitalization 24) . Another Canadian-based study focusing on work-related absences of one week or greater found older workers were less likely to report income from workers' compensation sources in the year of their absence or the year following their absence 23) .…”
Section: Discussionmentioning
confidence: 99%